Detection of clostridium tetani in human clinical samples using tetX specific primers targeting the neurotoxin - Ganesh, Madhu; Sheikh, Nasira K.; Shah, Pooja; Mehetre, Gajanan T.; Dharne, Mahesh S.; Nagoba, Basavraj S. (Journal of Infection and Public Health, 2016)
Tetanus resulting from ear injury remains an important health problem, particularly in the developing world. We report the successful detection of Clostridium tetani using tetX specific primers targeting the Cl. tetani neurotoxin. The sample was obtained from an ear discharge of a case of otogenic tetanus in a 2-year-old male child. Based on the culture results of the ear discharge, Gram staining and virulence testing by genotyping, a diagnosis of tetanus was confirmed. This is the first report from India on the successful detection of Cl. tetani in a human clinical sample using tetX specific primers targeting the Cl. tetani neurotoxin. (C) 2015 King Saud Bin Abdulaziz University for Health Sciences. Published by Elsevier Limited. All rights reserved.
Keywords: Cl. tetani; Neurotoxin; Otogenic tetanus; Trismus